Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Tetap Pada Dinas Kependudukan Dan Pencatatan Sipil Provinsi DKI Jakarta - Dinda Tiara Eka Martaya; Novita Wahyu Setyawati; Indah Rizki Maulia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The aim of this research is to determine the influence of work discipline and work motivation on employee performance. The type of research used in this research is quantitative research using the SPSS 24 application. The number of samples in this research is 37 respondents who are service and archives employees at the Population and Civil Registration Service of DKI Jakarta Province. Data analysis techniques in this research use validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of this research show that: (1) work discipline has a positive and significant effect on employee performance. (2) work motivation has a positive and significant effect on employee performance. (3) work discipline and work motivation simultaneously have a positive and significant effect on employee performance. The contribution of work discipline and work motivation to employee performance is 0.545 or 54.5%.